VERBAL AND NON-VERBAL SIGNS OF LANGUAGE IN ADVERTISEMENTS: A SEMIOTIC APPROACH OF TEACHING - Ni Wayan Sukarini; Maria Gorethy Nie Nie (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
This paper takes semiotic as a possi[te practical approach toward the teaching oflanguage through its verbal and nonverbal signs. Semiotic is the study of signs (verbal and nonverbal) and signs are mostly used in advertisements not even in Public Service Advertisements (PSA). The use of verbal and nonverbal signs is to deliver the messages to the intended audiences. The language learners can understand the messages being delivered through sentences rvhich are mostly performed through verbs at the beginning. The form is imperative forms with the function of persuading. PSA of HIV/AIDS was chosen as the data source because of one among some reasons: based on the statistics number of victim suffered from HIV/AIDS is increasing all over the rvorld. It is a qualitative research and the data was taken from electronic media (internet) through the methods of obsen'ation and documentation. The theories of semiotic, linguistics. and teaching method were applied for analyzing the data. The analysis rvas focus.ed on how verbal and nonverbal signs oflanguage which deliver messages can be effectively understood through semiotic approach of teaching. It is hoped that the findings of this paper will raise awareness of teachers as a foreign language to what constitutes the semiotic approach of teaching and how to apply it.